Pelatihan PELATIHAN PEMBELAJARAN KLINIK TERINTEGRASI DENGAN MENGGUNAKAN MODUL YANG BERBASIS PENDEKATAN SYMPTOM PADA PRECEPTOR DI PUSKESMAS - Siti Munawaroh; Veronika Ika Budiastuti; Eti Poncorini Pamungkasari; Atik Maftuhah; Dian Nugroho; Maria Sekar Cahyaningrum; Stefanus Erdana Putra; Muhammad Hafidzan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
Primary healthcare is one of the vehicles in learning for students of the medical profession. The preceptor clinic in primary healthcare is expected to guide and direct students studying there so that it can be effective. Integrated learning in all fields of medical science that is applied is expected to prepare medical graduates who are ready to enter the community. The symptom and sign approach is considered one of the effective methods in learning primary healthcare. Therefore, we intend to provide integrated clinical learning training using a module based on the symptom approach at primary healthcare. This community service involves ten primary healthcare located in the Boyolali and Klaten areas. The activity begins with exploring the problems that exist when guiding students of the medical profession who study primary healthcare. Then proceed with introducing guidance methods using clinical learning guides with a sign and symptom approach and ends with training evaluations. The participants of this activity received this training and provided some input regarding the existing modules. Suggestions from the primary healthcare preceptors were used as input to improve the modules that had been prepared.